A Highly Versatile and Adaptable Artificial Leaf with Floatability and Planar Compact Design Applicable in Various Natural Environments. Issue 34 (17th July 2017) - Kim, Sangkuk; Kim, Taewan; Lee, Seunghyup; Baek, Seunghyeon; Park, Taiho; Yong, Kijung
Abstract : As a promising means of solar energy conversion, photovoltaic (PV) cell‐based electrolysis has recently drawn considerable attention for its effective solar fuel generation; especially the generation of hydrogen by solar water splitting. Inspired by remarkable accomplishments in enhancing the solar‐to‐hydrogen conversion efficiency, various efforts have aimed at fostering convenient and practical uses of PV electrolysis to make this technology ubiquitous, manageable, and efficient. Here, the design and function of a monolithic photoelectrolysis system—a so‐called artificial leaf—for use in various environments are highlighted. The uniquely designed artificial‐leaf system facilitates an unbiased water‐splitting reaction by combining superstrate PV cells in series with single‐face electrodes in a compact 2D catalytic configuration. Floatability is a new feature of the water‐splitting artificial leaf; this feature maximizes solar light utilization and allows for easy retrieval for recycling. Additionally, its planar design enables operation of the device in water‐scarce conditions. These characteristics endow the artificial leaf with versatility and a high adaptability to natural environments, widening the applicability of the device. Abstract : A highly versatile and adaptable artificial leaf with floatability and planar compact design applicable in various natural environments is developed. Floatability is a new feature of the water‐splitting artificial leaf; this feature maximizes solar light utilization and allows easy retrieval for recycling. Additionally, its planar design enables operation of the device in water‐scarce conditions.